City structure, search, and workers' job acceptance behavior - Sato, Yasuhiro (2004)
This paper develops a stochastic search model having a monocentric city structure and investigates how city structure affects workers' job acceptance behavior and a labor market. In the model, workers reside in a city and commute to the Central Business District (CBD) to work when employed and to be interviewed when unemployed. When a job searcher contacts a firm having a vacant job, he/she observes the level of training costs necessary for employment and decides whether to accept the job. It is shown that there exists a unique market equilibrium in which the employed live close to the CBD and the unemployed reside far away from the CBD. Analysis shows that (1) improvement of commuting technology induces job searchers to accept more costly jobs and lowers the unemployment rate in the city, (2) growth of the city makes job searchers less tolerant of training and raises the unemployment rate, and (3) as job searchers search more intensively, they become choosier if commuting costs are sufficiently small. Efficiency properties of the equilibrium are also explored. - Reproduced.
Keywords: Employment; Labour market; Unemployment; Labour market